PENGARUH PENGGUNAAN GADGET TERHADAP PERKEMBANGAN KOGNITIF SISWA KELAS VI MADRASAH IBTIDAIYAH KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Ridwanudin; Lestari, Hana; Huda, Samsul (Prodi PGMI IAI Sahid, 2025)
This study aims to determine the effect of the use of gadgets on the cognitive development of grade VI students of Madrasah Ibtidaiyah, Pamijahan District, Bogor. This study used a quantitative approach with the correlation method and simple linear regression technique. The subjects of this study were students of Madrasah Ibtidaiyah Class VI Pamijahan Bogor District consisting of eleven schools with a sum of 302 student samples. Data collection techniques are carried out through questionnaires and documentation. The results showed an R square value of 0.096 (9.6%) showing that the independent variable (gadget use) had an influence on the dependent variable (cognitive development) by 9.6%. While 90.4% is influenced by other variables. The r interpretation proves the effect of gadget use on cognitive development is in the very low category with a coefficient interval of 0.00-0.199. The results of the t test found that t count < t table (1.676 < 1.968) then H1 rejected statistically is not significant, from the results of the t test a significant value greater than 0.05 (0.095> 0.05) means that there is no significant influence between the use of gadgets on cognitive development.